The conjugates of forky peptides and nonsteroidal anti-inflammatory drugs (NSAID) self-assemble into supramolecular hydrogels for prostate cancer-specific drug delivery. Issue 3 (20th December 2018) - Tao, Mingtao; He, Suyun; Liu, Jing; Li, Hongmei; Mei, Leixia; Wu, Can; Xu, Keming; Zhong, Wenying
Abstract : Herein, we report supramolecular hydrogelators made of forky peptides and nonsteroidal anti-inflammatory drugs (NSAID). Abstract : Herein, we report supramolecular hydrogelators made of forky peptides and nonsteroidal anti-inflammatory drugs (NSAID). Two zinc ions (ZIs)-responsive short peptide dendrons (E3 FID and E3 FNP) modified by NSAID (indometacinand naproxen) were designed and synthesized successfully. These novel small molecule hydrogelators can self-assemble in water to form stable supramolecular nanofibers/hydrogels. The formation of these supramolecular hydrogels can be triggered by zinc ions, which are highly concentrated in prostate tissue. The anticancer drug docetaxel (DTX) was employed as chemotherapeutic and loaded into the hydrogels to construct a novel drug delivery system for prostate cancer therapy. This approach is anticipated realizing the sustained release of antitumour drugs into the prostate and cancer associated pain relief, simultaneously. The E3 FID hydrogel and E3 FNP hydrogel have excellent biocompatibility and viscoelastic properties as a promising drug delivery materials. The result of drugs release in vitro indicated that DTX was released slowly following a non-Fickian diffusion mechanism. In addition, the results of the in vitro cytotoxicity assay demonstrated that these DTX-loaded hydrogels exhibited dose-dependent cytotoxicity to both DU-145 cells and PC-3 cells, in particular, the drug-loaded hydrogel of E3 FID had better anticancer efficacy. As a drug delivery strategy, the system realizes better anticancer efficacy, excellent sustained-release and relief of cancer pain, simultaneously, the most important being that the DDS facilitates local delivery of drug to the prostate.